Evaluating selected soil hydraulic properties under varied land use types at the Arjo‐Dhidhessa Estate Sugar Factory, Western Ethiopia - Workina Geleta; Fekadu Fufa; Abdissa Bekele (Agrosystems, Geosciences & Environment)
Abstract This study investigates the effects of land use type and soil depth on soil hydraulic properties at the Arjo‐Dhidhessa Estate Sugar Factory, Western Ethiopia. Soil samples (15 composites) were collected from five land use types (fallow land, cropland, irrigated land, forest land, and shrub land) across three soil depths (0–30, 30–60, and 60–90 cm). Field infiltration rates were measured using a double ring infiltrometer. The study demonstrates significant variation in soil hydraulic properties that forestlands showed higher performance, with the highest field capacity (51.46%), an available water‐holding capacity (21.23%), and a soil moisture content (23.74%). Conversely, irrigated land indicated the lowest infiltration rates (19.6 cm/h) and sorptivity (75.3 cm/h), likely linked to soil compaction and nutrient depletion. Soil hydraulic properties also varied with depth, showing reduced water retention and infiltration in deeper layers (60–90 cm). These results underscore the importance of diverse land management strategies for optimizing soil health and water resource management. Integrating forest and shrubland practices can enhance organic content and improve soil composition. Further, implementing management techniques such as conservation tillage and replanting can mitigate soil loss and compaction, promoting sustainable agricultural production. This study demonstrates the critical role of land use in shaping soil hydraulic properties. The findings advocate for land management practices that prioritize soil health and water retention, particularly through the integration of forest and shrubland elements. By adopting these strategies, policymakers and land managers can foster long‐term agricultural sustainability in the face of ongoing land transformation.